The Strategies Used by English Teacher in Teaching Speaking at SMPN 8 Rokan IV Koto - Helfany Amsa (International Journal Of Pedagogical Novelty (IJOPNOV), 2022)
Speaking has the important role in life. All of students also need to know the importance of English speaking skill. By having good speaking skill, the students will be able to communicate each other and develop them to be wise speakers both in the class and daily life. There are many kinds of strategies applied by teacher in teaching speaking. But the teacher might select the strategy that appropriate with the students need. The strategy for teaching greatly affects the students’ understanding in a process of learning. The main purposes of this research what strategies teachers use in developing speaking skills and the reasons why students find it difficult to learn speaking. Researchers conduct the data by using observation and interview methods. From this study, researcher found that that the strategies used in learning speaking were role-play, group discussion and doing creative task